An Equilibrium Model of Search Unemployment - Albrecht, James W.; Axell, Bo (Journal of Political Economy, 1984)
This paper develops a simple general equilibrium model with sequential search in which a nondegenerate wage offer distribution is endogenously determined. We use this model to analyze the comparative statics effects of increases in unemployment compensation on the unemployment rate and aggregate welfare taking into account the induced change in the wage offer distribution. Our results differ significantly from the predictions of the standard "partial-partial" model. For example, one can expect a selective increase in unemployment compensation, made available to those who impute a relatively low value to leisure, to decrease the equilibrium rate of unemployment.